2004
DOI: 10.1210/en.2003-1241
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Differentiation in Embryoid Bodies Derived from Human Embryonic Stem Cells

Abstract: Trophoblast differentiation and early placental development are essential for the establishment of pregnancy, yet these critical events are not readily investigated in human pregnancy. We used embryoid bodies (EBs) prepared from human embryonic stem (hES) cells as an in vitro model of early human development. The levels of human chorionic gonadotropin (hCG), progesterone, and estradiol-17beta in medium from hES cell-derived EBs grown in suspension culture for 1 wk were higher than unconditioned culture medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 19 publications
11
150
0
5
Order By: Relevance
“…4 A and B). A rather similar phenomenon of disorganized differentiation occurs in EBs derived from hES cells (36). This pattern of differentiation is distinct from that occurring when hES colonies are treated with bone morphogenetic protein-4, which causes a synchronized and larger scale differentiation of trophoblast-like cells at the periphery of the colony (37).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…4 A and B). A rather similar phenomenon of disorganized differentiation occurs in EBs derived from hES cells (36). This pattern of differentiation is distinct from that occurring when hES colonies are treated with bone morphogenetic protein-4, which causes a synchronized and larger scale differentiation of trophoblast-like cells at the periphery of the colony (37).…”
Section: Discussionmentioning
confidence: 85%
“…hES cells can readily be induced to form EBs. To explore the effects of hypoxia on this conversion, H1 cells (Ϸ2 ϫ 10 6 cells per well), which had been maintained under hypoxic conditions for eight successive passages (passages [33][34][35][36][37][38][39][40], were compared for their ability to form EBs with an identical number of cells that had been maintained under normoxic conditions for a comparable time period. During the early stages of culture, both groups of cells formed dense, simple EBs (Fig.…”
Section: Production Of Afp Under Normoxic and Hypoxic Conditions Afpmentioning
confidence: 99%
“…Bisulfite reaction was carried out using the EpiTect bisulfite kit (Qiagen). The ELF5-2b promoter region was isolated using nested PCR as described previously (2). The primers used were as follows: first PCR forward, GGAA-ATGATGGATATTGAATTTGA; first PCR reverse, CAATA-AAAATAAAAACACCTATAACC; 2nd PCR forward, GAGG-TTTTAATATTGGGTTTATAATG; 2nd PCR reverse, ATAAATAACACCTACAAACAAATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis revealed that when compared with undifferentiated cells, many of the most highly up-regulated genes were associated with trophoblast function, particularly transcription factors (chiefly defined in mouse development), and endocrine markers of human trophoblast differentiation, including hCG, and enzymes important for steroid hormone synthesis (Gerami-Naini et al 2004). Interestingly, it has also been reported that the effect of BMP or related ligands on hESCs is very cell line dependent.…”
Section: Trophoblast Differentiation From Embryonic Stem Cells: Impormentioning
confidence: 99%
“…A second approach with H1 and H9 hESCs for trophoblast differentiation from hESCs was identified with subsequent studies (Gerami-Naini et al 2004). Reasoning that mimicking the spherical configuration of the preimplantation embryo with pluripotent hESCs may initiate signals parallel to those acting during preimplantation embryo development, we directed embryoid body (EB) formation by enzymatic release of undifferentiated ESC colonies from culture plates, and maintained them in suspension culture in bacterial grade culture dishes.…”
Section: Trophoblast Differentiation From Embryonic Stem Cells: Impormentioning
confidence: 99%